Research on Oversupply, Producer Decision and Price Fluctuation of Agricultural Products - Jianfeng Wei, Hongyu Luo, Pai Zhang, Zhiqiang Wu (Forest Chemicals Review)
The decision-making behaviour of agricultural producers is the basic factor affecting the price fluctuation of agricultural products. In order to explore the price decline mechanism of agricultural products and provide reference for producers’ decision-making, the equilibrium price model and price war model are used to analyze the pricing behaviour of producers, and the practical problems of price decline of some agricultural products in China are summarized. The research shows that under the market pressure of oversupply, price competition is carried out among producers, and price reduction becomes the only sales strategy; in China’s agricultural production, excessive entry into the agricultural market and certain exit barriers are the basic reasons for price falling. The range of price fluctuation is related to the product characteristics and production organization structure of agricultural products. Different from the existing studies, this study pays more attention to the pricing decision-making mechanism and non-cooperative game of producers, and analyzes the relationship between agricultural product characteristics, agricultural organization structure and price fluctuation.